Socially inclusive valorization of gold mill tailings from the small-scale gold mining sector - R.M. Balanay; R.P. Varela; A. Balbin; M.A. Lavapiez (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Gold mining wastes have long been a significant concern in Agusan del Sur, a gold mining district in the Philippines. The region is vulnerable to climate change effects such as typhoons and flooding, which may lead to contaminated runoff or overflow that could potentially harm the local agriculture and adjacent natural ecosystems. This study aims to analyze the properties of the gold mill tailings, investigate their potential for reutilization, and identify areas that need improvement in order to promote an inclusive approach towards the valorization of mine waste.METHODS: The samples were collected randomly from a small- scale gold mill tailings storage facility. The samples underwent analysis for elemental and oxide composition, particle dimensions, potential of hydrogen, lead, mercury, free cyanide and hexavalent chromium. A gap analysis was utilized to pinpoint the methods for enhancing a socially inclusive reuse strategy for the mill tailings.FINDINGS: The characterization of the tailings reveal that some heavy metals like zinc, titanium, copper, barium, and manganese, and hazardous substances like arsenic, mercury, and lead are present. Elevated levels of mercury, lead, and free cyanide were detected in the wastewater, with concentrations of 0.029 milligram per liter, 0.40 milligram per liter, and 1.9 milligram per liter, respectively, surpassing the allowable thresholds. There is a high risk of contaminating the neighboring ecosystem during flooding events and waste overflow. The tailings also contain fine particles of about 75 percent fine sand and 25 percent clay. Adequate maintenance of tailings storage facilities, community awareness of waste-related risks and hazards, legal frameworks and financial backing to encourage waste utilization, local community empowerment, and adherence to occupational health and safety guidelines in waste management are essential strategies to bridge existing disparities and foster a socially inclusive approach to mine waste valorization.CONCLUSION: The gold mill tailings contain hazardous substances and fine dust, potentially damaging the nearby ecosystem and community. It is essential to prioritize the maintenance of a well-managed tailings storage facility in order to avoid contamination. The reuse of gold mill waste tailings can bring about economic, social, and environmental advantages. However, there are gaps that must be addressed to achieve a socially inclusive gold mill waste circularization. The utmost importance should be placed on the health and safety aspect, and it is advisable to carry out a comprehensive investigation into the degree to which hazardous substances are polluting the surrounding ecosystem, including the local community.